TN

Tìm x, biết: \(16x^3-12x^2+3x-7=0\)

SN
12 tháng 9 2018 lúc 22:07

\(16x^3-12x^2+3x-7=0\)

\(\Leftrightarrow16x^3-16x^2-3x^2+3x+7x^2-7=0\)

\(\Leftrightarrow16x^2\left(x-1\right)-3x\left(x-1\right)+7\left(x-1\right)\left(x+1\right)=0\)

\(\Leftrightarrow16x^2\left(x-1\right)-3x\left(x-1\right)+\left(x-1\right)\left(7x+7\right)=0\)

\(\Leftrightarrow\left(x-1\right)\left(16x^2-3x+7x+7\right)=0\)

\(\Leftrightarrow\left(x-1\right)\left(16x^2+4x+7\right)=0\)

<=> x - 1 = 0 

<=> x = 1

Bình luận (0)
H24
12 tháng 9 2018 lúc 22:08

\(\Leftrightarrow16x^3-16x^2+4x^2-4x+7x-7=0\)

\(\Leftrightarrow16x^2.\left(x-1\right)+4x.\left(x-1\right)+7.\left(x-1\right)=0\)

\(\Leftrightarrow\left(x-1\right).\left(16x^2+4x+7\right)=0\)

Ta có \(16x^2+4x+7=\left(4x\right)^2+2.4x.\frac{1}{2}+\frac{1}{4}+\frac{27}{4}\)

\(=\left(4x+\frac{1}{2}\right)^2+\frac{27}{4}>0\)

nên \(\left(x-1\right).\left(16x^2+4x+7\right)=0\)

\(\Leftrightarrow x-1=0\)

\(\Rightarrow x=1\)

Bình luận (0)